2011
DOI: 10.1002/asia.201100763
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Dynamics and Solution Chemistry of Polyoxometalates by Electrospray Ionization Mass Spectrometry

Abstract: Mass spectrometry both complements other analytical techniques and allows for types of analyses and experiments not possible with common analytical methods, such as NMR, IR, and UV/Vis spectroscopy. Electrospray constitutes one of the mildest forms of ionization, making it the preferred method for the analysis of large fragile or reactive ions. There is particular promise for mass spectrometry in aiding the characterization of polyoxometalates and their solutions, but caution must be taken in designing the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…The last method has been reviewed recently for applications related to polyoxometalates by Ohlin 43 and there exist many good examples of the application. The series of steps accounts for much of the observed data on rates of isotope exchanges in oxo clusters like the niobate anions or aluminate cations.…”
Section: Isotope-exchange Dynamics: Nmr and Esi-msmentioning
confidence: 99%
See 2 more Smart Citations
“…The last method has been reviewed recently for applications related to polyoxometalates by Ohlin 43 and there exist many good examples of the application. The series of steps accounts for much of the observed data on rates of isotope exchanges in oxo clusters like the niobate anions or aluminate cations.…”
Section: Isotope-exchange Dynamics: Nmr and Esi-msmentioning
confidence: 99%
“…The series of steps accounts for much of the observed data on rates of isotope exchanges in oxo clusters like the niobate anions or aluminate cations. 43,44 In these plots, one can see clusters changing stoichiometry as a function of collision-induced dissociation or partial dissociation of a cluster. Counterions and solvation forces are important because charge separation is essential to forming the metastable structure.…”
Section: Isotope-exchange Dynamics: Nmr and Esi-msmentioning
confidence: 99%
See 1 more Smart Citation
“…NMR spectroscopy is not practical for most POMs because commonly incorporated metals are usually not well‐suited for such experiments and the cost of 17 O‐enriched water limits its use for the synthesis of isotopically labelled POMs . ESI‐MS is thus the most suitable and straightforward technique for the solution investigations for these types of compounds . Especially when the formation of different isomers, short‐lived reaction intermediates or products of low abundance complicate the analysis…”
Section: High‐nuclearity Pom Structures In Solutionmentioning
confidence: 99%
“…In this respect, use of soft ionization mass spectrometric techniques, and in particular, ESI techniques, is becoming widespread. Excellent reviews on the use of soft ionization MS techniques can be found elsewhere; for example, Cronin et al illustrated the versatility of ESI and cryospray ionization techniques not only for characterization of final POM assemblies, but also to prove mechanisms of self-assembly of supramolecular POM-based architectures in solution [47,50]. Ohlin et al reported an important work on this topic highlighting different approaches to obtain reliable information on the dynamic solution of POM on the basis of ESI-MS [47].…”
Section: Analytical Tools To Study Solution Speciation In Nb and Ta Pmentioning
confidence: 99%